(untitled) (Journal of Engineering, 2016)
Many problems are facing the installation of piles group in laboratory testing and the errors in results of load and settlement are measured experimentally may be happened due to select inadequate method of installation of piles group. There are three main methods of installation in-flight, pre-jacking and hammering methods. In order to find the correction factor between these methods the laboratory model tests were conducted on small-scale models. The parameters studied were the methods of installation (in-flight, pre-jacking and hammering method), the number of piles and in sandy soil in loose state. The results of experimental work show that the increase in the number of piles value led to increase in load carrying capacity of piled raft and decrease in settlement value for three methods of installation. The response of increases load capacity for hammering method is the same value of pre-jacking method at the number of piles less than (N=2), while when the number of piles are beyond (N=3 to 9). The load capacity of hammering method is more than pre-jacking method and the correction factor of method of installation depend on the type of method of installation and the piles number. The increase in carrying capacity by hammering method is due to mobilize the dynamic soil structure interaction (soil-pile and pile-pile interaction) and the change in properties for surrounding soil for loose state of sand is more effective than static soil structure interaction mobilize by pre-jacking method. The correction factor of increase in load capacity and the correction factor of the percentage of settlement reduction for pre-jacking and hammering methods are compared with in-flight method of installation are changed with the number of piles and these values are increased with increasing the number of piles.